Posterior Shoulder Instability in Tennis Players: Aetiology, Classification, Assessment and Management - Lyn Watson; Gregory Hoy; Timothy Wood; Tania Pizzari; Simon Balster; Shane Barwood; Sarah Ann Warby (International Journal of Sports Physical Therapy)
# Background